Repeat after me, my name is Javier: immigrants English prociency improvement four years after arrival - Torres, Javier (2013)
Proficiency in the host-country language is one of the most important assimilation dimensions for immigrants. This paper analyzes changes in the English proficiency of recent immigrants to Canada using a panel data of four years. Probit and ordered probit estimations show how specific characteristics relate to language proficiency improvement or decline. I use speaking abilities as an overall indicator of language proficiency and separate the sample according to immigrants' initial level: basic, intermediate or advanced. Overall, immigrants show relatively small improvements in language proficiency in the first four years. Still, those arriving under the family immigrant category with an intermediate or advanced level are less likely to improve and more likely to decrease their English proficiency. These results suggest that newcomers in this category experience a particularly different environment in the host country. The effect is not statistically robust for immigrants with a basic knowledge of English. advanced. Overall, immigrants show relatively small improvements in language pro ciency in the first four years. Still, those arriving under the family immigrant category with an intermediate or advanced level are less likely to improve and more likely to decrease their English pro ciency. These results suggest that newcomers in this category experience a particularly di erent environment in the host country. The ef ect is not statistically robust for immigrants with a basic knowledge of English.